Determinan Pending Claim Badan Penyelenggara Jaminan Sosial Kesehatan di Rumah Sakit - Nayada Ilfania Arokhta Yunifa; Achmad Jaelani Rusdi; Lilik Afifah (Jurnal Syntax Admiration, 2025)
Pending claims are a problem that still often occurs in Indonesia, where many hospitals face obstacles in the BPJS Kesehatan claim process. This problem can have a significant impact on the quality of health services. This study aims to analyze the factors that cause BPJS Kesehatan pending claims in hospitals. The method used is literature review by searching for articles through the Google Scholar database in the last five years. The study follows PRISMA guidelines and uses the PICO framework to determine inclusion and exclusion criteria. The keywords used in the search involve the operator's boolean: "Factor" AND "Pending Claim" OR "Return" AND "BPJS" OR "JKN". From the search results, 20 articles were found that were worthy of systematic review. The results of the review showed that 17 articles identified internal factors as the main cause of pending claims, especially the incompleteness of supporting documents such as laboratory results, ECG, and chronological letters. In addition, 19 articles revealed external factors as the main cause, namely lack of thoroughness and responsibility in carrying out tasks, such as data input errors, incompleteness in filling out medical resumes, and inaccuracies in diagnostic or action codes. Internal and external factors influence each other, so the right solutions are needed for every aspect, including improving the quality of documentation, improving the e-claim information system, and developing human resource competencies through training.